Modern Business Management Creating a Built-to-Change Organization - Dockery, Doug (Apress, 2018)
Transform your entire organization, not just a part of it. Take a modern look now that the world is focusing on business agility rather than thinking about team-level or even scaled Agile. Many people and businesses believe that "doing Agile" will solve all their business and organizational problems. The truth is that "doing Agile", especially team-level agility, is not the same as being an agile organization. Authors Doug Dockery and Laureen Knudsen share their years of experience in transforming corporations and organizations to successfully compete and win in today's fast-paced markets. Using proven techniques and stories of actual experiences in a multitude of organizations, Doug and Laureen relate what it takes to successfully transform your organization, as well as how to tell if your transformation is working. Modern Business Management details what you need to know to transform your business to deliver value and thrive. Coverage includes: What Agile means to an executive and the benefits you should be seeing The top failure modes and why so many transformations fail A framework for success, including an operational framework and a transformation framework How big data internal to a company is needed to successfully run a world-wide corporation today The definition of a modern business and what it looks like What You'll learn: Understand why businesses are not getting the benefits out of their current Agile transformation Follow the process that organizations need to go through to succeed See how C-level executives can benefit from Agile practices Know how to succeed where others are failing Discover how to keep up with a constantly disrupted and ever-changing market.